Etika Profetik Santri; Resepsi Hadis Pada Tradisi Pendidikan Pesantren - Farihin, Hibbi; Khasani, Fahim (J-PAI: Jurnal Pendidikan Agama Islam, 2023)
Pesantren is a place for students to build good character and study Islamic sciences deeply. The Traditions enforced in Pesantren for many years have moral values inspired by the hadith of the Prophet. Phenomena like this is part of the study of living hadith, which is an effort to gain knowledge about the culture, thoughts, behavior and traditions of the people inspired by the hadith of the Prophet. This article explores the daily ethics of santri which has become a tradition at PP. Hidayatul Mubtadi'in, Lirboyo-Kediri. By using the methods of observation, interview, and documentation, the research found that there were four categories of santri behavior that reflected the living hadith and had become a tradition in PP Lirboyo: Worshiping, Moral, Social and Environment. Among these phenomena, some are recognized as living hadith and some are not aware that the tradition has prophetic value. Exploring the phenomenon of living hadith today is very necessary in order to know the methodology of Nusantara scholars in Hadith reception and applying it in the real life.